Hubungan Aktivitas Fisik dan Pola Tidur dengan Kejadian Obesitas pada Anak Usia 10-18 Tahun - Hubaybah Hubaybah; Adelina Fitri; Fitria Eka Putri; Evy Wisudariani; Desi Ramadani (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2022)
Overweight or obesity is a condition caused by excessive food consumption accompanied by inadequate physical activity. Based on the United Nations Children's Fund (UNICEF) the level of obesity in several Southeast Asian countries also shows a fairly high rate, where Indonesia ranks second with the largest number of obese adolescents. Risk factors for the incidence of overweight or obesity in children are heredity, environment, intake, physical activity, psychological and lifestyle. lifestyle, for example food intake, physical activity, and the application of good sleep. The purpose of this study was to determine the relationship between physical activity and sleep patterns with the incidence of obesity in children aged 10-18 years in the working area of the Payo Selincah Health Center, Jambi City. This study used a type of quantitative research with a cross sectional research design. Data was collected in October-November 2021. The study population was 2,245 children aged 10-18 years with a research sample of 88 children. The sample was taken using Non Probability Sampling technique (Purposive sampling). This study consists of independent variables